Исследование эффективности экранирования гамма-излучения теллуридными стеклами, полученными методом твердофазного синтеза - Козловский, А.Л. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Study of the efficiency of gamma radiation shielding by telluride glasses obtained by solid-phase synthesis